Elements for water management in Zirahuen lake watershed. - Pascual Ramírez, Fermín; José Ríos, Mauricio; Mendoza Ramírez, Rosalva; Silva Casarín, Rodolfo; Simuta Champo, Roel; Reyes López, Delfino (REVISTA TERRA LATINOAMERICANA, 2018)
Knowledge of the phenomena that occur in a basin allows finding cause-effect relationships over time and space through modeling. One of the necessary steps is to determine elements that make up and directly influence runoff. These elements are the basis for planning and formulating strategies for the conservation and management of water resources. The main goal was to determine the current condition of the Zirahuén lake basin by studying collections of available information of the place of study. We collected physiographic, sociodemographic and geomorphological information in the official databases of public access, and geospatial processes were executed in conditioning and analysis of the information. It was found that despite the distribution in coverage and land use, the morphometric characteristics contribute to lake stability. If trends in population dynamics and land use continue, ecosystem survival could be threatened by the increase in population and productive activities that deteriorate and alter the hydrological cycle, with decreases in access to water, in quantity and quality, for essential human activities.